A Study of Identifying Trends in Projector using F-Term Codes from Japanese Patent Applications - Ishii, Yoshie; Kaminishi, Ken; Haruyama, Shigeyuki (International Journal of Integrated Engineering, 2021)
It is important for companies to understand technological trends when developing technologies and products. Based on Utterback and Abernathy's theory of the emergence of dominant design, we investigate a method of obtaining technological trends using patent information. In a previous study, we visualised the innovation state and obtained the emergence of dominant designs using FI and theme codes, which are original patent classification codes of Japanese patents, as well as F-terms. However, there has not been sufficient research conducted on how to obtain patent applications and how to select FIs, theme codes, and F-terms, which are the preconditions for the analysis. In this study, we discuss a procedure for obtaining patent applications, selecting FIs, theme codes and F-terms, visualising the innovation state, and predicting the emergence of dominant designs, and report the results.